Gambaran Paparan Media Sosial Instagram, Pengetahuan, Sikap dan Perilaku Merokok pada Siswa MAN 2 Kota Tangerang Tahun 2024 - Nurfajriah, Indri; Aristi, Dela (Journal of Religion and Public Health, 2024)
Smoking is one of the public health problems. Data from the Indonesian Health Survey in  2023  showed  that  the  prevalence  of  smokers  aged  15-19  years  was  56.5%,  while according  to  BPS  in  2023  smokers  in  Tangerang  City  were  14.79%.  Exposure  to negative  information  and  content  on  Instagram  can  have  both  positive  and  negative effects  on  its  users.  The  purpose  of  this  study  was  to  determine  the  description  of exposure to  Instagram  social  media,  knowledge,  attitudes  and  smoking  behavior  in adolescents  at  MAN  2  Tangerang  City  in  2024.  This  type  of  research  is  quantitative with  a  cross  sectional  design  approach.  Data  analysis  in  the  study  used  univariate tests. The sample in the study were MAN 2 Tangerang City students in grades X and XI of 157 respondents. The results showed that smoking behavior in students was 17.2%. The  level  of  knowledge  of  respondents  about  the  dangers  of  smoking  is  mostly  good 54.8%. The majority of respondents' attitudes towards smoking behavior were positive 53.5%. Exposure to negative cigarette content on Instagram social media on students amounted  to  81.5%.  Students  are  exposed  to  educational  content  on  the  dangers  of smoking  on  social  mediaInstagram  93%. Therefore,  schools  are  expected  to  provide guidance   or   education   to   all   students   regarding   smoking   behavior   by   utilizing Instagram  social  media.  Educational  content  can  be  done  by  posting  videos,  posters, and pictures.Keywords: Adolescent, Instagram, Smoking behavior.